Using Community Indicators to Assess Nutrition in Arizona-Mexico Border Communities - Jacob Abarca, PharmD; Sulabha Ramachandran, MS (Centers for Disease Control and Prevention, 2005)
Introduction Community indicators are used to measure and monitor factors that affect the well-being of a community or region. Community indicators can be used to assess nutrition. Evaluating nutrition in communities along the Arizona-Mexico border is important because nutrition is related to an individuals risk of overweight or obesity; obesity is a risk factor for developing type 2 diabetes. Methods Local grocery store purchases were selected as a community indicator for nutrition. A structured 26-question interview was developed and administered to grocery store managers in communities along the Arizona-Mexico border that were targeted by the Border Health Strategic Initiative, a program implemented by community groups and the University of Arizona. In addition, data from milk distributors serving the border communities were collected. Results Residents of these communities favor food items with a higher fat and higher caloric content. This trend held across several food categories. Major barriers to customer acceptance of healthier food items include lack of knowledge concerning healthy foods and their prices. Conclusion The demand for healthy food items is relatively low along the Arizona-Mexico border. Interventions should continue to target this population with the aim of changing dietary patterns as one method of improving the health of the community and preventing and controlling diabetes.